PROFESSIONAL COMMUNICATION AND ITS ROLE IN LIBRARY DEVELOPMENT: A STUDY - Rokade, S.M. (International Journal of Research -GRANTHAALAYAH, 2016)
The paper succinctly describes the term Professional communication, different types of managers of libraries, type of institutions and their users, sources used by the librarian for professional communication and its role in library development. The survey was carried out through personal communication and discussion and was observed that computer, Internet, Intranet, Ethernet, email, mobile and TV are the 100 % main means of library professional communication and 93.33 % SMS , 91.11 % work, 85.55 % seminar, 75.55 % Twitter, 61.11% articles, 56.66 % verbal, 54 % meeting, 48.33 % membership of associations, 47 % written, 30.55 share it, 30 % meeting, 26 % fax, 25 % chat and program, 12.22 % VoIP, 18.88 survey, 17.77 speeches, 11.11 % radio, 8.33 blog, 6.66 messages were used by the library professionals for transfer and distribute of information and exchange of knowledge, ideas, and experiences amongst themselves. The four types of attitudes observed in professional communication i.e. Passive, Passive Aggressive, Aggressive, and Assertive. The professional communication maintains interrelation and avoids misunderstandings and is quite useful for the development of library.